Clinical Practice Trends and Postoperative Outcomes in Primary Cleft Rhinoplasty. (August 2022) - Jazayeri, Hossein E.; Lopez, Joseph; Pourtaheri, Navid; Lee, Kevin C.; Peck, Connor J.; Best, David L.; Yu, Jason W.; Gosain, Arun K.; Peacock, Zachary S.; Edwards, Sean P.; Steinbacher, Derek M.
Purpose: Optimal correction of the cleft nasal deformity remains challenging. The purpose of this study was to examine the practice patterns and postoperative course of patients undergoing cleft lip repair with rhinoplasty compared to those who have primary lip repair without rhinoplasty. Methods and Materials: A retrospective cohort study was conducted based on the Kids' Inpatient Database. Data were collected from January 2000 to December 2011 and included infants aged 12 months and younger who underwent cleft lip repair. The predictor variable was the addition of rhinoplasty at primary cleft lip repair. Primary outcome variables included hospital setting, year, and admission cost, while secondary outcome variables included length of stay and postoperative complication rate. Independent t -tests and chi-squared tests were performed. Continuous variables were analyzed by multiple linear regression models. Results: The study sample included 4559 infants with 1422 (31.2%) who underwent primary cleft rhinoplasty. Over time, there was a significant increase in the proportion of cleft lip repairs accompanied by a rhinoplasty ( p  < .01). A greater proportion of patients with unilateral cleft lips received simultaneous rhinoplasty with their lip repairs (33.8 vs 26.0%, p  < .01). This cohort had a significantly shorter length of stay (1.6 vs 2.8 days, p  < .01) when compared to children that underwent cleft lip repair alone. Conclusions: Performing primary cleft rhinoplasty is becoming more common among cleft surgeons. Considering comparable costs and complication rates, a rhinoplasty should be considered during the surgical treatment planning of patients with cleft nasal deformities.